Multifunctional Micro/Nanofiber Based‐Dressing Patch with Healing, Protection, and Monitoring Capabilities for Advanced Wound Care (Adv. Mater. Technol. 7/2023). Issue 7 (6th April 2023) - Ha, Ji‐Hwan; Kim, Jae Yun; Kim, Dahong; Ahn, Junseong; Jeong, Yongrok; Ko, Jiwoo; Hwang, Soonhyoung; Jeon, Sohee; Jung, Young; Gu, Jimin; Han, Hyeonseok; Choi, Jungrak; et al.
Abstract : Multifunctional Wound Dressings In article number 2201765, Ji‐Hwan Ha, Jun‐Ho Jeong, Inkyu Park, and colleagues present a multifunctional micro/nanofiber‐based dressing patch containing natural materials such as hyaluronic acid, gelatin, dexpanthenol, and curcumin for advanced wound care. The multifunctional wound dressing patch fabricated by an electrospinning process enables rapid wound healing, wound protection against external microbial, and wound status monitoring by colorimetric pH sensing.